Penggunaan Otosidal Ovitrap Untuk PengendaliaNyamuk Vektor Penyakit Demam Berdarah Denguen - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT The aim of this activity is to support the rural community at Ngeblak, Wijirejo, Pandak Sub district, Bantul District, Yogyakarta to overcome the Dengue Haemorrhagic Fever (DHF) problem by controlling the vector continuously to reduce population density of Aedes aegypty and Aedes albopictus by application of otocidal ovitraps. Regarding this point a serial activity as follows has been conducted (1) preliminary survey to investigate population density of Aedes (breteau Index) or B1 and Larvae Free Index (LFI)